Relationship between decomposition level and induced solidification of peat based on laboratory investigation - Abd Rahman, Junita (2015)
Over 60 % of Pontian district is covered by peat. Peat is considered as a poor quality soil for construction due to the high moisture content and low bearing capacity. Solidification of peat is important in this area before any construction work could start thus, will increase the population rate in the district. The degree of decomposition affects the porosity of peat while the porosity is affected by both particle size and structure of the peat. The pores between the decomposed materials in peat can be filled and bound using ordinary portland cement (OPC) and coal ash (fly ash, FA and bottom ash, BA). Different decomposition levels of peat require different amounts of filler and binder to achieve the optimum strength. The peats are categorized as fabric for the less decomposed peat, hemic for the moderately decomposed and sapric for the mostly decomposed peat. The Pontian peat has high moisture content with fabric peat having 970 %, hemic peat, 417 % and sapric peat, 720 %. All peat was found acidic with pH 3-4.5 while the binders and filler are in alkaline state. The physico-chemical and mechanical properties of peat were identified according to British (BS 1377, 1990) and US (ASTM, 2000) standards. Chemical tests were adopted from previous researchers to identify the chemical properties. The mixtures of peat-binder-filler were subjected to the unconfined compressive strength (UCS) test, bender element (BE) test and the same chemical tests as applied for the original sample. The mix ratios examined were of four types being 100 % OPC, 50 % OPC 50 % BA, 50 % OPC 25 % BA 25 % FA and 25 % OPC 50 % BA 25 % FA. Two water-binder ratios were used, i.e. 1 and 3. Curing periods of 7, 14, 28 and 56 days were applied for all samples. The moisture content of the peat was controlled at 300 % before mixing. The scanning electron microscope (SEM) result shows that over time, the peat was filled with calcium silicate hydrate (CSH) and calcium aluminate hydrate (CAH) which were products of cement hydration. The strength gain for fabric peat is 157 kPa, while hemic peat, 737 kPa and sapric peat, 121 kPa. It is concluded that regardless the peat decomposition level, the optimum for a peat-binder-filler mixture to get the significant strength, should consist of i) 23 - 34 % of particles, being combination of peat fiber and BA with size ranging from 2 mm to 0.15 mm, ii) OPC with equal amount of dry mass of the peat and iii) 25 % of FA by the total mass of binder. This combination was found to be effective for the peat-binder-filler mixture. Keywords: Peat decomposition level, bottom ash, fly ash, OPC, solidification.